Implementasi aplikasi kehadiran perkuliahan dikelas menggunakan pembaca RFID pada e-KTP - Muhamad Akbar; Irman Effendy (Politeknik Harapan Bersama, 2018)
This research was conducted to help the process of teaching and learning in the classroom by utilizing the information obtained from class attendance e-KTP reader. E-ID card now has a chip that can be used and owned by students to solve class attendance problem. In this research, information that obtained from e-KTP is used as application input. This research built an application that can read the information saved in the e-KTP chip card, then used as the student class attendance counter. The descriptive and qualitative methodology was used in this research. This research aimed to help the university stakeholder to effectively and efficiently monitor students and lecturers attendance.